Bridget Jones : mad about the boy - Fielding, Helen, 1958- (Alfred A. Knopf, 2013)
Londonite Bridger Jones faces the challenges of maintaining sex appeal as the years roll by, the nightmares of drunken texting, the skinny jean, the disastrous e-mail cc, total lack of Twitter followers, and TVs that need ninety buttons and three remotes to simply turn on.